2012
DOI: 10.1136/emermed-2012-201285
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of rapid point-of-care creatinine testing for the prevention of contrast-induced nephropathy in the emergency department

Abstract: This study suggests that POCT-BUN/Cr results correlate well with those of serum reference tests in terms of BUN and Cr levels and, in turn, predicting CIN. POCT-BUN/Cr is easily performed with a rapid turnaround time, suggesting its use in the ED may have substantial clinical benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 14 publications
(25 reference statements)
1
14
0
Order By: Relevance
“…118 Although POCT is a particularly attractive option in remote and low resource environments, it requires the implementation of a quality assurance program that ensures accurate and reliable results. Several POCTs for Scr are available in the market across the world 116,118–124 and can be classified into blood gas analyzers and nonblood gas analyzers. They also vary with respect to the types of samples that can be processed—whole blood, plasma, or serum.…”
Section: Point-of-care Testingmentioning
confidence: 99%
“…118 Although POCT is a particularly attractive option in remote and low resource environments, it requires the implementation of a quality assurance program that ensures accurate and reliable results. Several POCTs for Scr are available in the market across the world 116,118–124 and can be classified into blood gas analyzers and nonblood gas analyzers. They also vary with respect to the types of samples that can be processed—whole blood, plasma, or serum.…”
Section: Point-of-care Testingmentioning
confidence: 99%
“…You et al performed a retrospective analysis of patients with suspected stroke over a 1-year interval from November 2009 to November 2010 and found that the blood urea nitrogen and creatinine determined in their emergency department correlated well with determination by the hospital central laboratory of the same blood chemistries. 17 These authors emphasized the possible importance of the rapid point-of-care determination for predicting the risk of CI-AKI.…”
Section: General Prevention Of Contrast Damage To the Kidneysmentioning
confidence: 99%
“…Contrast-induced nephropathy (CIN) is a known complication of procedures in which intravascular iodinated contrast media are administrated [1,2]. Patients with preexisting renal impairment have an increased risk of developing CIN.…”
Section: Introduction/backgroundmentioning
confidence: 99%